EXTENDED SPECTRUM BETA LACTAMASE - A RISING THREAT IN URINARY TRACT INFECTIONS - RAO VIDHYA,; RAO SUNIL PADMARAJ, (International Journal of Pharma and Bio Sciences, 2014)
Antibiotic resistant urinary tract infections are increasing in frequency with Extended Spectrum beta Lactamase (ESBL) producing organisms on the rise. Routine antibiotic susceptibility testing may fail to detect these strains, leading to treatment failures. This study aims at the detection and analysis of ESBL producing Gram negative bacteria in hospitalized patients with UTI.Mid-stream clean catch urine samples from 600 patients with symptoms of hospital acquired UTI were subjected to culture and antimicrobial susceptibility testing by standard methods. ESBL production was confirmed by standard CLSI guidelines. E.coli (47.1%) was the predominant pathogen. Sixty ESBL producers were found and all were sensitive only to Imipenem. Beta-lactam with beta-lactamase inhibitor combination was also found to be effective. Co-resistance to two or more other classes of drugs along with the third generation cephalosporin resistance indicates multi-drug resistance in these strains.ESBL producing Gram negative bacilli are a serious challenge because of their changing trend, multi-drug resistance and their frequent isolation in hospital acquired UTI. For the therapeutic benefit in resistant cases, additional confirmatory tests for screening ESBL will be of great use.